Yesus, Perantau dari Surga: Sebuah Usaha Awal Meninjau Kristologi Injil Yohanes dari Sudut Pandang Imigrasi - Ekaputra Tupamahu (Indonesian Journal of Theology, 2015)
This article registers a preliminary effort to (re)construct Christology in the Gospel of John from a migrant perspective. Jesus is "the Stranger" who immigrates to the earth from heaven. He is not only a migrant, John also describes him as an unwanted and rejected foreigner. Special attention is given to the paradoxical relationship between Jesus and the world. The seemingly paradoxical tension the Gospel of John describes is better explained, this article will argue, when Jesus is conceived as an immigrant.